Engineering and Durability Properties of Modified Coconut Shell Concrete - Trokon Cooper Herring; Joseph N. Thuo; Timothy Nyomboi (Civil Engineering Journal, 2022)
Making low-cost concrete from coconut shell ash and coconut shell aggregate increases sustainability and reduces pollution. This research investigates untreated Coconut Shell Particles (CSP) incorporated with coconut shell ash (CSA) to improve the durability properties at elevated temperatures and in sulphuric acid. Initially, the physical and mechanical properties of cube and cylinder specimens after 7, 28, 56, and 90 days of moist curing were studied. The durability properties were then carried out after the pozzolanic component of CSA in modified concrete was activated. CSA and CSP were used as partial substitutes for ordinary Portland cement and coarse aggregate in class 30 concrete with a constant water to cement ratio of 0.55. Concrete mixes included control, 5% CSP, 10% CSA, and a mixture of 5% CSP incorporated with 10% CSA. According to test results, adding 10% of CSA to CSP concrete decreased the workability, density, and water absorption properties compared to the rest of the concrete mixes. However, these results were within acceptable limits. The compressive strength of 10% CSA concrete at 90 days of moist curing was reduced by 3.23% when 5% CSP was added compared to control. The addition of 10% of CSA to 5% CSP concrete improved the split tensile strength by 2.76% higher than concrete with only 5% CSP. Concrete containing the combination of 10% CSA and 5% CSP showed a 9.37% increment in the split tensile strength compared to concrete having only 5% CSP after sulphuric acid exposure. Also, the compressive strength of 10% CSA and 5% CSP concrete improved by 30.7% when the temperature was elevated to 500 °C for 1 hour compared to the control concrete. Moreover, the reduction in the compressive strength after exposure to the elevated temperature of 500 °C for 1 hr. was still much less by an average of 75.38% compared to other waste materials blended into the concrete by previous works. Doi: 10.28991/CEJ-2022-08-02-013 Full Text: PDF